Race Matters: 1968 as Living History in the Black Freedom Struggle - Jorrit van den Berk; Laura Visser-Maessen (European Journal of American Studies)
New questions about the legacies of 1968 and the 1960s in general are presenting themselves to us, as scholars and as citizens, ever more urgently. This is particularly true of race and racial struggle, as unresolved race matters from the past poignantly intersect with twenty-first century activism aimed at countering the continued devaluation of black lives. This special issue of The European Journal of American Studies focuses on the black freedom struggle to explore how those “unresolved race matters from the past” weigh down on the present in terms of (dis)continuities in political activism, protest cultures, backlash, and memory and to highlight the ways in which the 1960s continue to inform and inspire explanations of and resistance to the racial status quo in the 21st century. This introduction will explain why and categorize how today’s racial landscape has shaped contemporary societal and scholarly interest in the black, and especially radical, activism of 1968.